Decision Making in Interactive Learning Environments Towards an Integrated Model - Qudrat-Ullah, Hassan; Karakul, Mustafa (Journal of decision systems, 2007)
Experimental research on decision making and learning in dynamic tasks with the use of computer-simulation-based interactive learning environments as DSS is analyzed. A conceptual model encompassing key elements of decision making: decision, decision maker, and decision making process is constructed. The model draws on two sources: (1) the dynamic decision making literature and (2) a relevant learning theory- cognitive apprenticeship. Departing from traditional dynamic decision making research focus on how poorly subjects perform in dynamic tasks, our model, through acquisition-of-expertise hypothesis, attempts to increase our understanding of the way in which expertise on dynamic decision making could be acquired through training with computer-simulation-based interactive learning environments.